Measuring the Economic Impact of COVID-19 with Real-Time Electricity Indicators - Vagliasindi, Maria (World Bank, Washington, DC, 2021)
The COVID-19 pandemic is posing unprecedented challenges, making it difficult for policy makers to design appropriate policies. In this context, real-time information can play a most valuable role for policy makers in developing countries, particularly since official economic indicators, such as the evolution of GDP and unemployment, not only are released with considerable delays, but also are not always fully reliable. This paper follows the literature by using the dependent variable electricity consumption per capita as a proxy measure of economic activity in the short run. Based on this method, it examines the short-run economic impact of the pandemic itself, as well as the public health restrictions that were adopted to control the outbreak and the macro-economic measures applied to revive the economy. The analysis confirms the significant cost of lockdown measures in terms of reduction in economic activity but finds that the spread of the disease itself had an economic impact distinct from that of the lockdown measures. The analysis shows that the use of expansionary fiscal and monetary policies also played a key role in mitigating such an impact, driving some initial recovery. Finally, the evidence points to a complete structural break in economic activity at the onset of the lockdown period.